JOKI TUGAS KULIAH DARING DI KALANGAN MAHASISWA - Rabathy, Qisthy; Elly Komala; Taufik Hidayatullah (Linimasa : Jurnal Ilmu Komunikasi, 2023)
The implementation of online lectures due to the Covid-19 pandemic has created various problems for students, such as using lecture assignment jockey services among students to help complete assignments because there are many assignments with short deadlines. The rapid development of information and communication technology has made it easier for jockeys to offer their services, especially through social media applications. This research was conducted to determine the motives, actions, and meaning of the students who became task jockeys. The study was conducted using a phenomenological approach with a descriptive qualitative method. The results of this study indicate that in the concept of motive, first, the reason behind jockeying online lecture assignments among students is the motive of helping, gaining a material benefit, and filling in spare time activities. Second, the motive is to obtain non-material benefits to improve and develop skills, abilities, and knowledge. The act of assignment jockey is carried out by waiting for other people based on friend recommendations, asking friends who have been assisted in recommending their services to others, and promoting their services openly through social media. Meanwhile, in a meaning, students who become jockeys for online lecture assignments are activities to help others in doing their coursework which was originally motivated by the aim of providing assistance, which then received material rewards, as well as a way for them to improve their abilities and skills, especially in the academic field.